Starch/Gum Arabic Blends for Controlled Drug Delivery and Cancer Therapy: Synthesis and Characterization - Ismaeel Moslam Alwaan (Journal of Global Pharma Technology, 2019)
Cancer is one of the most mortal diseases in the world .This work was planned to prepare a new chemical cross linking starch/gum Arabic hydrogel system in the presence of potassium persulfate(K2S2O8)as initiator, to describe the characteristic of the new material , and to investigate its potential utilizations in controlled drug delivery and cancer therapy. Crosslinked starch /gum Arabic hydrogel will be manufacture with changeable levels of starch and gum Arabic then were loaded with hydroxyurea. The structure of the native starch and starch/gum Arabic blends was characterized by FTIR, SEM. The starch and starch/gum Arabic blends were analyzed for in vitro drug release studies by using UV-vis spectroscopy. The swelling test, MTT assay were also investigated. The drug release and swelling test was monitored at pH 4 and pH7.4. The experimental results proved that the production of starch/gum Arabic blends was reduced the swell ability which lead to slow release of hydroxyurea, and the rate of hydroxyurea release was significantly higher at pH 7.4 than pH4, at constant incubation time. The swelling ratio and drug release of the blends was decreased with increasing gum Arabic levels. In vitro cytotoxicity study show the killing of 14âˆ¼